Low dose cadmium (II) induced antifungal activity against blast disease in rice. (December 2019) - Jali, Pallavi; Acharya, Srinivas; Mahalik, Gyanranjan; Pradhan, Chinmay; Das, Anath Bandhu
Abstract: The present approach in this study aims to check infection of Pyricularia oryzae (MTCC-1477) in a rice cultivar (Khandagiri) by applying low dose (50 μM) cadmium (II). In co-stress of Pyricularia oryzae and cadmium, the plants showed increased growth of shoot length and accumulation of protein, reducing sugar, photosynthetic pigments and antioxidative enzymes indicating improved growth and development at par with control plants. The co-stress induced increase in Phenylammonia lyase activity up to 752.01 U/mg protein and decrease in lipid peroxidation up to 15.81 μg/g, this activity strengthen the idea of enhanced innate defense mechanism of the plant against the pathogen. Antioxidant enzymes demonstrated enhanced activity and number of isoforms in co-stress indicative index for better performance. Two protein bands of MW 23 kDa and 47 kDa were more pronounced in the fungal and Cd treatment respectively. But the most affected band of MW 23 kDa disappeared due to co-stress, which may be designated as a Pathogen Related protein. The study under present experimental conditions is a trade off approach to next generation sustainable agriculture keeping in mind about rapid changing climate and alarming growth of environmental pollution. Graphical abstract: Image 1 Highlights: This article provides an idea regarding possible protection of the crop plant rice against blast disease with exposure of low dose of cadmium (II). In co-stress ( Pyricularia oryzae and cadmium) the plants showed increased accumulation of physio-chemical parameters indicating improved growth and development at par with control plants there by reducing the effect of fungal pathogenicity. Interestingly the co-stress induced increase in Phenylammonia lyase activity upto 752.01 U/mg protein and decrease in lipid peroxidation upto 15.81 μg/g, this activity suggesting a possible enhanced innate defense mechanism of the plant against the pathogen. Two protein bands of MW 23 kDa and 47 kDa were more pronounced in the fungal and Cd treatment respectively. But the most affected band of MW 23 kDa disappeared due to co-stress, which may be designated as a Pathogen Related protein. The present study is a trade off approach to next generation sustainable agriculture keeping in mind about rapid changing climate and alarming growth of environmental pollution.